Privacy, Dependency, Discegenation: Toward a Sexual Culture for People with Intellectual Disabilities - Adams, Rachel (Disability Studies Quarterly, 2015)
Monica and David, (Alexandra Codina 2010), Girlfriend (Justin Lerner 2010), and Me Too [Yo también] (Antonio Naharro and Álvaro Pastor, 2009) are recent films that explore the need for companionship, intimacy, and sexual expression among people with intellectual disabilities. They break ground in showing people with intellectual disabilities as capable of sexual agency as well as sustaining committed, mutually satisfying relationships. However they also consider the meaning of sex in the context of dependency. More challenging still, they probe the taboo of "discegenation," sex in which only one partner is disabled. In doing so, they raise complicated questions about consent, desire, and privacy in all sexual encounters.